The Innovation Factory - Start-up Catch 22's - Marion, Tucker J. (Senate Hall, 2007)
The case uses the rise and growing pains of a consumer product based company from 2000 to 2003 to highlight the ever-constant struggles of developing new products and building a consumer products company - juxtaposed with the difficulty of satisfying the desires of all parties, ranging from investors to customers. The company, known as the Innovation Factory grew dramatically in its first several years. Building on its successes, the company raised the capital needed to increase sales significantly. Product development issues, sales goals, investor needs, and operational challenges are outlined as the Innovation Factory progresses towards a third sales cycle. The case discusses the business, operational, and developmental strategies and pitfalls experienced during company growth and sets the stage for the major push for increased sales in the coming year.
Keywords: entrepreneurship|startup|product development|growth